2022
DOI: 10.3389/fphar.2022.862709
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanism of Naringenin Against High-Glucose-Induced Vascular Smooth Muscle Cells Proliferation and Migration Based on Network Pharmacology and Transcriptomic Analyses

Abstract: Although the protective effects of naringenin (Nar) on vascular smooth muscle cells (VSMCs) have been confirmed, whether it has anti-proliferation and anti-migration effects in high-glucose-induced VSMCs has remained unclear. This study aimed to clarify the potential targets and molecular mechanism of Nar when used to treat high-glucose-induced vasculopathy based on transcriptomics, network pharmacology, molecular docking, and in vivo and in vitro assays. We found that Nar has visible anti-proliferation and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…5A ). Creb5 is a crucial component of the downstream signaling pathway of PI3K/AKT 32 . It is a member of the Creb (cAMP-responsive element-binding protein) family of proteins 33 .…”
Section: Resultsmentioning
confidence: 99%
“…5A ). Creb5 is a crucial component of the downstream signaling pathway of PI3K/AKT 32 . It is a member of the Creb (cAMP-responsive element-binding protein) family of proteins 33 .…”
Section: Resultsmentioning
confidence: 99%
“…As such, additional studies on these other genes and their association with CREB5 expression are important and could provide insights, especially on their role in GBM progression. Meanwhile, in recent studies it was reported that high glucose can activate the PI3K/Akt/CREB5 signaling pathway, resulting in excessive proliferation and migration of vascular smooth muscle cells [ 37 ]. Identifying the upstream regulatory elements that affect CREB5 expression and activity in GBM is also necessary.…”
Section: Discussionmentioning
confidence: 99%
“…This effect involves β2-AR-dependent pathways involved in the control of CREB activity downstream of GSK3β ( 13 ). Furthermore, He et al ’s analysis showed that CREB5 is a downstream protein of the PI3K/Akt pathway that participates in vascular smooth muscle cells’ proliferation and migration which may lead to cardiomyocyte hypertrophy ( 14 ). In our study, we found that downregulation of hsa-miR-1244 and upregulation of hsa-miR-217 reduced upregulation of CREB5, and both effects were related to downregulation of SNH12.…”
Section: Discussionmentioning
confidence: 99%